PENGARUH PWHT TERHADAP SIFAT MEKANIK PADA SAMBUNGAN LAS TAK SEJENIS AUSTENITIC STAINLESS STEEL DAN BAJA KARBON - , AGOES DUNIAWAN, ST ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Welding of dissimilar metals between austenitic stainless steel and carbon steel has been widely used in railways, automotive, ship, and many other engineering fields. Austenitic Stainless Steel has properties of high toughness at low temperature, good corrosion resistance, good machinability and good weldability while low carbon steel has properties of high strength and good machinability. However, Austenitic Stainless Steel becomes brittle when it is welded due to precipitation of Chromium Carbide (Cr23C6) at austenite grain boundary. This precipitation occurs due to slow welded-cooling rate from temperature of 900 degree C to 450 degree C. On the other hand, low carbon steel has excessive hardening in HAZ if high welded cooling rate is employed decreasing in toughness. This research aims to improve mechanical properties of weld joint of Austenitic Stainless Steel with Carbon Steel by means of Post-Welding Heat Treatment (PWHT) process. AISI304 stainless steel and low Carbon steel plates were welded using MIG welding whith a filler of ER308,voltage 19 Volt, current of 100 Ampere DC,heat input of 1 kJ/mm and welding speed of 2 mm/s welding speed. PWHT at temperature of 450 degree C ,550 degree C and 650 degree C for 3 hours were done after welding process . Microhardness test, microstructure test, tensile test,toughness test,and SEM were then conducted on the weld specimen. The result shows that increasing in PWHT temperature increases a toughness of weld area, meanwhile HAZ area toughness increases of PWHT temperature of 450 degree C